The non-invariant time and Lorentz-like transformations - Boris Čulina (Revista Brasileira de Ensino de Física)
From the comparison of time in inertial frames, possible types of transformations between inertial frames are deduced. This elementary deduction directly relates the properties of time with the type of transformations. When all inertial frames measure the same time (time is absolute), the transformations are Galilean. When each inertial frame has its own time, different from the times of other inertial frames (time is not invariant) the transformations are Lorentz-like with the same positive parameter k. The parameter k is the supremum of possible velocities in an inertial frame, the same for all inertial frames. Einstein’s postulate about the invariance of the speed of light says more: there is a uniform motion with the supremum k, which is exactly the motion of light in a vacuum. At the end of the article, attempts to reduce the special theory of relativity to the principle of relativity are criticized.